Functionally thrombasthenic state in normal platelets following the administration of ticlopidine. - Di Minno, G (1985)
To elucidate the bleeding tendency that follows the administration of ticlopidine, we investigated the skin bleeding time and some ex vivo functions of platelets obtained from eight healthy volunteers before and 1 wk after daily administration of 500 mg of ticlopidine. We found the following: ticlopidine significantly (P less than 0.001) prolonged the skin bleeding time and impaired the binding of radiolabeled fibrinogen and von Willebrand Factor, the clot retraction and the aggregation of platelets in response to ADP, epinephrine, thrombin, ionophore A23187, collagen, or arachidonic acid. In contrast, the administration of this drug did not affect intraplatelet levels of cAMP, agglutination and binding of von Willebrand Factor in response to ristocetin, shape change in response to ADP, collagen, thrombin, or arachidonic acid, or binding of prostaglandin E1 to resting platelets. Secretion of ATP in response to ADP or epinephrine was completely inhibited, whereas secretion as well as thromboxane synthesis in response to high concentrations of collagen, arachidonic acid, calcium ionophore A23187, or thrombin was unaffected. Studies with monoclonal antibodies showed that the glycoprotein IIb-IIIa complex (the putative receptor for fibrinogen and von Willebrand Factor on the surface of platelets exposed to naturally occurring aggregating agents) was quantitatively unaffected by ticlopidine. This observation was further confirmed by densitometric scannings of Periodic Acid-Schiff-stained gels of platelet suspensions. The onset, as well as the cessation of the inhibitory effect of ticlopidine on platelets was very slow, and reached a maximum after a 3-5-d administration. In addition, ticlopidine appeared to be a much more potent inhibitor when administered to subjects than when added in vitro to platelets. Finally, abnormalities comparable to those found in volunteers taking ticlopidine were observed when platelets from untreated subjects were incubated in the plasma of ticlopidine-treated subjects. We conclude that ticlopidine induces a thrombasthenic state in normal platelets without affecting the glycoprotein IIb-IIIa complex quantitatively. Furthermore, our data suggest that one or more active metabolites rather than the native drug mediate the abnormalities of platelet function observed in ticlopidine-treated subjects.